Rules for the use of unused leave - Majchrzak, Katarzyna (Prawo Kanoniczne, 2018)
The employer is obliged to grant the employee a leave in the calendar year in which the employee obtained the right to have it. It is in accordance with the principle stipulated in art. 152 § 1 of the Labor Code. However, this principle is not always implemented in practice. Therefore, in accordance with art. 168 of the Labor Code, the employer may grant unused leave for a current year by the end of the third quarter of the following year. Granting unused leave by September 30th does not apply to the part of a leave which was not used by an employee at their request. It is regarded that a deadline for granting an unused leave by the end of September of the following year is kept when 30th of September is the first day of granted unused leave. Not granting the employee's outstanding leave in the above-mentioned time is an offense against the employee's rights. Responsibility for this offense is in principle borne by the employer. Therefore, it should be agreed with the view that the employer may grant overdue leave, even if the employee does not agree to the use of this leave within this period.